PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI MADRASAH ALIYAH ARIFAH GOWA - Annisa F, Nurul; Kasmawati, Andi; Rifdan, Rifdan (Jurnal Tomalebbi, 2024)
This research aims to: (1) Understand the Implementation of Principal Academic Supervision Activities in improving Teacher Pedagogical Competence at MA Arifah Gowa. (2) Knowing the techniques of school principals as supervisors in improving teacher pedagogic competence at MA Arifah Gowa. (3) Knowing the supporting and inhibiting factors in implementing teacher pedagogical competency improvement at MA Arifah Gowa. This type of research is qualitative research with a descriptive approach. The sources for this research are the principal, head of curriculum, and teachers. Data collection techniques are carried out through observation, interviews and documentation. Checking the validity of the data uses data source triangulation techniques. The results of the research prove that (1) The implementation of the principal's academic supervision activities in improving the pedagogic competence of teachers at MA Arifah Gowa is a) the planning stage, b) the implementation stage, and c) the follow-up stage. (2) Techniques for Implementing Supervision Activities carried out by the Principal as Supervisor in Improving Teacher Pedagogical Competence, namely with individual and group technical strategies. (3) Supporting and Inhibiting Factors in the implementation of academic supervision activities by school principals in improving teachers' pedagogical competence, including a) Supporting Factors including the support of the school principal, a variety of learning media, the existence of teacher motivation, facilities and infrastructure. b) Inhibiting factors, namely education financing factors.